Between music and dance: Dalcroze and the Moving Plastic (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Translation of the text La Rythmique, la Plastique Animée et la Danse written by Émile Jaques-Dalcroze and originally published in 1916. The translation is preceded by a historical contextualization of the text and the main themes it addresses, namely: the conceptual assumptions of Jaques-Dalcroze method (known as Eurhythmics and based on rhythmic body and vocal exercises); the foundations of Moving Plastic and its developments in the field of theatrical staging; the aesthetic and pedagogical problems of dance and the becoming of a new dance.
Keywords: Jaques-Dalcroze (1865-1950); eurhythmics; body; Moving Plastic; dance